2021
DOI: 10.48550/arxiv.2101.10061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Closed $\mathrm{G}_2$-eigenforms and exact $\mathrm{G}_2$-structures

Marco Freibert,
Simon Salamon

Abstract: A study is made of left-invariant G 2 -structures with an exact 3-form on a Lie group G whose Lie algebra g admits a codimension-one nilpotent ideal h. It is shown that such a Lie group G cannot admit a left-invariant closed G 2 -eigenform for the Laplacian and that any compact solvmanifold Γ\G arising from G does not admit an (invariant) exact G 2 -structure. We also classify the seven-dimensional Lie algebras g with codimension-one ideal equal to the complex Heisenberg Lie algebra which admit exact G 2 -stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…There are also several classes of exact G 2 -Structures on non-compact manifolds that have recently been produced. Examples on unimodular Lie algebras with vanishing third Betti number are considered by Fernandez, Fino, and Raffero [26], and examples which are closed G 2 -Eigenforms are considered by Friebert and Salamon [27]. It is worthwhile to note that there are no compact quotients of the unimodular Lie algebra examples, and it is known that a compact manifold cannot admit closed G 2 -eigenforms [12].…”
Section: Ric(gmentioning
confidence: 99%
“…There are also several classes of exact G 2 -Structures on non-compact manifolds that have recently been produced. Examples on unimodular Lie algebras with vanishing third Betti number are considered by Fernandez, Fino, and Raffero [26], and examples which are closed G 2 -Eigenforms are considered by Friebert and Salamon [27]. It is worthwhile to note that there are no compact quotients of the unimodular Lie algebra examples, and it is known that a compact manifold cannot admit closed G 2 -eigenforms [12].…”
Section: Ric(gmentioning
confidence: 99%
“…Assume now that ϕ is an exact G 2 -structure on g = s ⋊ D R, namely ϕ = dα for some α ∈ Λ 2 g * . By [13], we know that if g is strongly unimodular, then the solvable ideal s is not nilpotent. We can write α = α + β ∧ η, where α ∈ Λ 2 s * and β ∈ s * .…”
Section: The Solvable Casementioning
confidence: 99%
“…However, it is still not known whether exact G 2 -structures may occur on compact 7-manifolds. A negative answer to this problem was given in [10,13] in some special cases. In [10], M. Fernández and the first and third named author of this paper proved that there are no compact examples of the form (Γ\G, ϕ), where G is a simply connected solvable Lie group with (2, 3)-trivial Lie algebra g, namely b 2 (g) = 0 = b 3 (g), Γ ⊂ G is a cocompact discrete subgroup (lattice), and ϕ is an invariant exact G 2 -structure on Γ\G, namely it is induced by a left-invariant exact G 2 -structure on G. In [13], Freibert and Salamon showed that the same conclusion holds, more generally, when the Lie algebra of G admits a codimension-one nilpotent ideal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations